Quark and gluon spin-2 form factors to two-loops in QCD - de Florian, Daniel Enrique (2014)
We present complete two-loop radiative corrections to the graviton-quarkantiquark form factor G∗ → q q and graviton-gluon-gluon form factor G∗ → g g in SU(N) gauge theory with nf light flavours using d-dimensional regularisation to all orders in ε = d−4. This is an important ingredient to next-to-next-to-leading order QCD corrections to hadronic scattering processes in models with large extra-dimensions where Kaluza-Klein graviton modes couple to Standard Model fields. We show that these form factors obey Sudakov integro-differential equation and the resulting cusp, collinear and soft anomalous dimensions coincide with those of electroweak vector boson and gluon form factors. We also find the universal behaviour of the infrared singularities in accordance with the proposal by Catani.